S39 COVID-19 incidence and hospitalisation in routine clinical practice among asthma patients in England in 2020. (11th November 2022) - Rothnie, KJ; Tritton, T; Han, X; Holbrook, T; Numbere, B; Ford, AF; Massey, L; Fu, Q; Hutchinson, FM; Birch, HJ; Leather, D; Sharma, R; et al.
Abstract : Introduction/Objectives: Evidence regarding the risk of severe COVID-19 illness among individuals with asthma is limited with some studies reporting an increased risk of severe illness among patients with asthma, and others finding no difference in the risk of severe illness between patients with asthma and those without. This study described the changes over time in COVID-19 diagnosis and hospitalisations due to COVID-19 among patients with asthma in England. Methods: This was a retrospective dynamic cohort study of English asthma patients aged ≥18 years, observed from March–August 2020, using the Clinical Practice Research Datalink Aurum database linked to Hospital Episode Statistics datasets. Monthly incidence rates of COVID-19 diagnosis and inpatient hospitalisations due to COVID-19 were described for all patients and stratified by 2019 GINA treatment step at baseline. Results: In total, 823, 645 incident and prevalent asthma patients (mean [SD] age: 51.4 [17.7] years, 58.1% females) were included; 21.3%, 3.9%, 23.6%, 12.7%, 3.1% and 35.4% of patients were in GINA step 1/2, GINA step 2, GINA step 3, GINA step 4, GINA step 5 treatment step and in the unclassifiable group, respectively, at baseline. Monthly rates of COVID-19 diagnosis and hospitalisation due to COVID-19 are shown in figure 1 . The incidence rate (95% CI) of COVID-19 hospitalisation per 100, 000 person-days for the March–August 2020 period by GINA treatment step was: GINA step 1/2 (1.0 [0.9, 1.2]); GINA step 2 (1.3 [1.0, 1.6]); GINA step 3 (1.6 [1.5, 1.7]); GINA step 4 (2.8 [2.6, 3.1]); and GINA step 5 (2.9 [2.4, 3.5]). Conclusion: Among patients with asthma, COVID-19 diagnosis rates peaked in April 2020, declined steeply to June 2020 and remained low through to August 2020. COVID-19 hospitalisation rates were substantially higher in patients with more severe asthma and highest among patients in GINA step 5 treatment group. Future studies on the long-term impact of COVID-19 in asthma are warranted. Please refer to page A209 for declarations of interest related to this abstract.